2017
DOI: 10.1111/nmo.13250
|View full text |Cite
|
Sign up to set email alerts
|

Insights on efficacious doses of PAMORAs for patients on chronic opioid therapy or opioid‐naïve patients

Abstract: Opioid-naïve subjects require a higher dose of PAMORA than chronic opioid users to achieve μ-opioid antagonist effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…An analysis of efficacious doses of PAMORAs for the inhibition of opioid analgesic effects on small bowel and colonic transit, as well as on symptoms related to OIC or postoperative ileus, shows that the doses required for efficacy are typically 1 log lower for chronic opioidtreated patients compared with opioid-naïve patients. 29 Our results on naloxegol are consistent with similar findings in prior studies on other PAMORAs: the approved dose of methylnaltrexone (0.30 mg/ kg SQ) to treat OIC in patients on chronic opioid therapy does not appear to reverse the inhibitory effect of codeine on colonic motility in opioid-naïve healthy volunteers, and a higher dose may be needed in that setting. 30 Indeed, a pharmacodynamics trial demonstrated reversal of morphine-induced delay in orocecal transit time (measured by lactulose-breath hydrogen) with a methylnaltrexone dose 50% higher (0.45 mg/kg) than the approved dose of 0.30 mg/kg.…”
Section: Discussionsupporting
confidence: 90%
“…An analysis of efficacious doses of PAMORAs for the inhibition of opioid analgesic effects on small bowel and colonic transit, as well as on symptoms related to OIC or postoperative ileus, shows that the doses required for efficacy are typically 1 log lower for chronic opioidtreated patients compared with opioid-naïve patients. 29 Our results on naloxegol are consistent with similar findings in prior studies on other PAMORAs: the approved dose of methylnaltrexone (0.30 mg/ kg SQ) to treat OIC in patients on chronic opioid therapy does not appear to reverse the inhibitory effect of codeine on colonic motility in opioid-naïve healthy volunteers, and a higher dose may be needed in that setting. 30 Indeed, a pharmacodynamics trial demonstrated reversal of morphine-induced delay in orocecal transit time (measured by lactulose-breath hydrogen) with a methylnaltrexone dose 50% higher (0.45 mg/kg) than the approved dose of 0.30 mg/kg.…”
Section: Discussionsupporting
confidence: 90%
“…P-glycoprotein transporter transports naloxegol from the central nervous system. 34 On a mg/kg dose comparison, naloxegol was approximately 33 times less potent than naloxone at antagonising effects of morphine in the gastrointestinal tract. 35 Naloxegol was 3.4-fold more potent than methylnaltrexone as an antagonist on human µ-opioid receptors.…”
Section: Pamora-peripheral µ-Opioid Receptor Antagonistmentioning
confidence: 95%
“…Four approaches are used for prophylaxis and treatment of opioid‐induced constipation: first, over‐the‐counter agents 15,16 or agents approved for the treatment of chronic constipation specifically linaclotide, prucalopride and lubiprostone (the latter also approved for treatment of opioid‐induced constipation); second, use of alternative opioids such as tapentadol (an enterally acting µ‐opioid receptor agonist and norepinephrine reuptake inhibitor 17 ); third, use of a fixed combination of opioid and opioid antagonist such as oxycodone‐naloxone and, fourth, use of peripherally acting mu‐opioid receptor antagonists (PAMORAs) 18,19 . The pharmacology of medications used in opioid‐induced constipation appears in Box 1 20‐35 . It is relevant to note that naloxone can enter the brain and it is theoretically conceivable that it may reverse analgesia or cause opiate withdrawal; however, the risk of this happening has not been assessed relative to other treatments used for opioid‐induced constipation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opioid medications are agonists for μ, κ, and δ opioid receptors, all of which are G protein coupled receptors . Activation of these receptors reduces neuronal excitability by causing hyperpolarization, with effects noted on excitatory, inhibitory, and secretomotor neurons throughout the gastrointesetinal tract .…”
Section: Introductionmentioning
confidence: 99%